Navigating the Legal Environment of Cannabis Law: Considerations for a Workplace Policy - Zugelder, Michael T. (American Journal of Management, 2022)
American law governing cannabis usage continues to suffer from the lack of a uniform national standard, as regulation has largely been left to the lawmakers of individual states and localities. At a time when public acceptance of personal use is on a rapid rise, many employers find themselves with the task of complying with multiple conflicting laws, while still trying to meet management objectives. A viable and sustainable workplace cannabis policy must be crafted to comply with this complex legal environment, that balances priorities of safety and loss prevention with the need for staffing, positive employee morale, and a firm image.